Environmental impacts of public policies in Campo Grande, MS: the case of Lajeado stream environmental protection area - Figueiredo, Helder Pereira de; Constantino, Michel Ângelo; Sanches, Cristiane Camargo; Costa, Reginaldo Brito da (Interações, 2016)
The post-agenda 2015 of the United Nations has focused on the environment based on the definition of Sustainable Development Goals (SDGs). This study aims to analyse which were the positive and negative externalities generated by public policies in the environmental scope between 2000 and 2015 in the Environmental Protection Area (EPA) of the Lageado area in Campo Grande, MS, from photographic records, satellite images and direct survey with beneficiaries.